Clinical Outcomes of Sequential Intrastromal Corneal Ring Segments and an Extended Range of Vision Intraocular Lens Implantation in Patients with Keratoconus and Cataract - C. Lisa; R. Zaldivar; A. Fernández-Vega Cueto; R. M. Sanchez-Avila; D. Madrid-Costa; J. F. Alfonso (Journal of Ophthalmology)
Purpose. To evaluate efficacy, safety, and predictability of sequential Ferrara-type intrastromal corneal ring segments (ICRS) and an extended range of vision intraocular lens (IOL) implantation in patients with keratoconus and cataract. Methods. This study comprised patients with keratoconus and cataract that had ICRS implantation followed 6 months later by extended range of vision IOL implantation. The uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), and residual refractive errors, analysed using vector analysis, were recorded preoperatively, 6 months after ICRS implantation, and 6 months after IOL implantation, respectively. Results. The study enrolled 17 eyes (11 patients). The mean UDVA (logMAR scale) was 1.15 ± 0.67 preoperatively, 0.88 ± 0.69 six months after ICRS implantation (P=0.005), and 0.27 ± 0.18 six months after IOL implantation (P<0.0001). The CDVA changed from 0.26 ± 0.15 (logMAR) before surgery to 0.17 ± 0.08 six months after Ferrara-type ICRS implantation (P=0.002) and to 0.07 ± 0.06 six months after IOL implantation (P<0.0001). The spherical equivalent and the refractive cylinder declined steeply after IOL implantation (P<0.001). The magnitude of depth of focus was 2.60 ± 1.02 D. There were no statistically significant differences in visual acuity for a defocus range from +0.50 D to −0.50 D (P>0.1). Conclusion. Sequential Ferrara-type ICRS and an extended range of vision IOL implantation provided good visual and refractive outcomes, being an effective, safe, and predictable procedure for the treatment of selected cases of patients with keratoconus and cataract. In addition, this approach provides an increase of tolerance to defocus.